(3OQhS hJeGQjfs - (3eMeO GdCejf(B, (3LHdjs ((3GdLRGFQ(B:s (3GdfTQ GdLGeYj GdLOjO(B,s, 2019)
(3jSJgOa gPG GdcJGH GdWdHI GdLGeYjjf ddWhQ GdChd (B((3d(B.(3e(B.(3O(B) (3, hJfbSe gPg GdeMGVQGJ Gdi NeSI eMGhQ CSGSjI , fSJgdgG HGdJhWFI deYQaI eaghe GdEbJUGO hGdeTcdI GdGbJUGOjI hef Cjf jfHKb Yde GdGbJUGO GdLRFj, CeG GdeMhQ GdKGfj acQS dcd eG jJYdb HSdhc GdeSJgdc hGdefaYI hefMfjGJ GdShGA hZjQgG(B. (3CeG GdeMhQ GdKGdK aMGhdfG GdLeY Hjf fXQjI GdWdH hfXQjI GdYQV dfage cja jJe JhGRf GdShb, hejcGfjRe Yed GdeQhfGJ , hcd eGjDKQ Ydi JhGRf GdShb, CeG GdeMhQ GdQGHY acGf dOQGSI Sdhc GdefJL ShGA aj GdeOi GdbUjQ Ch GdWhjd, hCNjQG GdeMhQ GdNGeS NUU dOQGSI fXQjI JGdJcGdja(B. (3dJcJed HgPG cGaI GdeYGde GdechfI debjGS GdGbJUGO GdLRFj(B.s
(3GdeQGLY U(B.165s
Keywords: (3GdEbJUGO GdLRFjs